2017
DOI: 10.1017/s1473550417000246
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic microorganisms in astrobiological analogue environments: from field site to culture collection

Abstract: Astrobiology seeks to understand the limits of life and to determine the physiology of organisms in order to better assess the habitability of other worlds. To successfully achieve these goals we require microorganisms from environments on Earth that approximate to extraterrestrial environments in terms of physical and/or chemical conditions. The most challenging of these environments with respect to sample collection, isolation and cultivation of microorganisms are anoxic environments. In this paper, an appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 68 publications
0
42
0
Order By: Relevance
“…Stress effects, such as low water availability, nutrients deficiencies, high levels of solar radiation, and wide temperature fluctuations in the surface soil of the Mojave Desert lead to the formation of physiological survival strategies for prokaryotes existing under these conditions [2,3]. Our study revealed a high diversity (both taxonomic and morphophysiological) of culturable bacteria in the investigated soil.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Stress effects, such as low water availability, nutrients deficiencies, high levels of solar radiation, and wide temperature fluctuations in the surface soil of the Mojave Desert lead to the formation of physiological survival strategies for prokaryotes existing under these conditions [2,3]. Our study revealed a high diversity (both taxonomic and morphophysiological) of culturable bacteria in the investigated soil.…”
Section: Discussionmentioning
confidence: 69%
“…One of the main tasks of modern astrobiology is studying environmental factors of different space bodies and outer space and to determine surviving and functioning limits of terrestrial life forms under extraterrestrial conditions [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Inside the chamber there is a thermocouple (5) for temperature control. The chamber together with the liquid nitrogen tank is thermally insulated with a syntepon bounded by an isilone cylinder (1). The chamber can maintain a pressure of ~0.01 Torr and a temperature of about −130 °C.…”
Section: Description Of the Climatic Chambermentioning
confidence: 99%
“…TPC-The samples, exposed to the low pressure and low temperature without irradiation. 1 The strain was isolated earlier in the course of other studies, see Section 2.1.…”
Section: Survivability Of Pure Bacterial Cultures Under Gamma Irradiamentioning
confidence: 99%
See 1 more Smart Citation